Afghan Migration and its Impacts on Community of Afghanistan - Badr, Waris; Ahmad, Ali; Aziz, Noorullah (Integrated Journal for Research in Arts and Humanities, 2023)
The history of migration is by far one of the very harshest and difficult topics in this new era of modernization. This article is going to define a particular part of the migration history and its aspects, which will be focusing mainly on a far-distant and barely remembered land called Afghanistan. Here we take you to the times of despair and hopelessness of a nation which has had war over war, conflict over conflict and which has seen empires come and go for over 3 centuries. This article talks about the poor condition of those people who had no other option but to leave their lands, harvests and sometimes even families because they were harmed by the war. What happens when one flees their country? Why would someone be this desperate? How does one deal with this inconvenience? What are the impacts of this immigration on a country? Do they ever return? The role of the neighboring countries has always been a very important issue in this topic like these. They have since been receiving our desperate and turmoil people who were in need of a shelter and asking for help for their survival’s sake. It will be unprofessional to just talk about their help and not their benefits from this vast immigration. They have also availed from our immigration. Pakistan and Iran have had very faithful and scared people working for them for a very less expensive wages which in other case would never have been the same.